Dziecko w konwencji roli – aspekt werbalny - Kuszak, Kinga (Wydawnictwo Naukowe UAM, 2015)
The article describes Erving Goffman’s approach to the concept of a dramaturgical model of social relations. The author briefly presents the general framework of the concept (stage, actors, role convention, mask, audience, etc.), focusing in more detail on the verbal aspect of a social role. She highlights the way children, through participation in interactions with parents, preschool teachers and peers, master the rules of various social roles and transpose the experiences gained through these interactions into other social situations, e.g. transposing the rules of linguistic politeness mastered in preschool into the home environment, using specific linguistic means to influence other members of the household. Theoretical reflections are illustrated with examples of preschool-aged children’s utterances indicating their mastery of the specific features of a given role. In the last part of the article, the author presents examples of children transgressing the convention of a role, which are a result of either the children’s lack of knowledge about the convention or their conscious action against adults’ expectations and attempts to manifest their own independence or verify to what extent the convention is of a universal nature and to what extent it can be modified.
Child in the Role Convention – the Verbal Aspect
Keywords: Erving Goffman’s concept; dramaturgical model of social relations; preschool-aged child in social relations; communicative competence; child’s communication with adults and peers